Freeze–thaw durability of high strength concrete under deicer salt exposure. (15th January 2016) - Liu, Zhichao; Hansen, Will
Highlights: Simultaneous measurement on surface scaling and moisture uptake is undertaken. HSC mixes are more prone to internal damage, albeit the high scaling resistance. A bi-linear pattern is noted for mass loss and moisture uptake of HSC mixes. Air-void characteristics is not a major factor in surface scaling of HSC mixes. Abstract: Freeze–thaw resistance of high strength concrete (HSC) and normal strength concrete (NSC) mixes with varying air contents was investigated by moisture uptake, mass loss and internal damage measurements. Sufficiently air-entrained HSC mixes demonstrate significant improvement in salt frost scaling resistance and the characteristics of air-void system is not a major factor. This can be attributed to the reduced capillary porosity and connectivity which curtails ice-growth promoted by capillary suction of surface liquid under freezing. A clear bi-linear pattern is found for the mass loss and moisture uptake curves of HSC mixes, the transition point of which coincides with each other. This demonstrates the importance of initial moisture condition in concrete prior to F–T test. Increased imperviousness of HSC to moisture ingress renders it more prone to long-term frost damage intrinsically, which is evidenced by much higher initial freezing strain in HSC from the length-change measurement on thin specimens at various degrees of saturation levels.